Organizational resilience factors in Bogotá-based businesses during the Covid-19 pandemic - Valbuena, Pedro Nel; Montenegro, Yamile Andrea Montenegro; González, Mario Hernán; Cendales, Boris (Cuadernos de Administración, 2023)
This article reports on descriptive case studies, and researched the factors of improvisation in organizational resilience in the context of the Covid-19 health emergency. A total of 23 businesses in the city of Bogotá, from different economic activities, participated in this study. Participants were managers, owners, legal representatives, or executives from those businesses. The research type is descriptive with a qualitative approach, aimed at identifying qualitative attributes based on responses or ratings using the Likert scale. A Likert-type questionnaire was used, rating seven resilience factors, whose indicators were defined by reviewing the literature on the subject. It was found that among the resilience factors, those with the lowest performance were the components of sustainability, corporate culture, and innovative ecosystem; the determinants of coping skills and leadership were the best performing; meanwhile, human talent and the elements of flexibility and adaptation played an intermediate role in sustaining the business amid the health emergency. The study corroborates the previously existing theory and shows the possible variation in the influence of improvisation factors depending on the size of the company, its structure and organization. This study may serve as an input for future research related to the determining factors in organizational resilience and the behavior of companies in the face of different types of crises.